Coagulase-negative staphylococci: Diversity, antimicrobial resistance and their role in human disease - Pinheiro, Luiza [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (My University, 2014)
Coagulase-negative staphylococci (CoNS) are opportunistic bacteria that can cause infections in immunocompromised patients who often use medical devices. These infections are mainly due to the formation of a biofilm. The aim of this chapter was to describe the diversity of CoNS, evolution of antimicrobial resistance, and the role of these microorganisms in human disease in order to provide data for future studies. Themain species of this group are: Staphylococcus epidermidis, the species most frequently isolated from blood cultures; S. haemolyticus, the second most frequent species which is associated with high antimicrobial resistance; S. hominis, an important cause ofbacteremia; S. warneri which has been related to multiple infections; S. lugdunensis which causes infections that are as severe as those caused by S. aureus, and S. saprophyticus, an usual cause of urinary infections in young women. CoNS exhibit high antimicrobial resistance, reaching 91% for penicillin. Resistance rates to methicillin/oxacillin of up to 96% have been reported in S. haemolyticus. Penicillin resistance is encoded by the blaZ gene, whereas methicillin resistance is mediated by PBP2a, a product of the mecA gene. The latter gene is carried by a mobile genetic element, SCCmec. This element is easily transferred among staphylococcal strains. Themethods used to detect oxacillin resistance are less effective because of the occurrence of vheteroresistance and mecA gene detection continues to be the gold standard. Although rare, reduced vancomycin susceptibility in CoNS is a matter of concern since this drug is one of the last therapeutic options for multidrug-resistant infections. Vancomycin heteroresistance is frequent in CoNS and cell wall thickening is the main underlying mechanism. The van genes, transferable elements found in enterococci, also encode resistance to the glycopeptides vancomycin and teicoplanin. New antimicrobials, including linezolid, daptomycin and tigecycline, show good efficacy against CoNS, although some studies already found strains resistant to linezolid and daptomycin and strains exhibiting high tigecycline minimum inhibitory concentrations. MLSB (macrolides, lincosamides, and streptogramin B) resistance, which is mediated by different mechanisms, can reach 66% in CoNS. Resistance rates to fluoroquinolones of 61.9%, to aminoglycosides of 42%, and to trimethoprim/sulfamethoxazole of 68% have been reported. Therefore, in view of the uncontrolled use of antimicrobials and continuous increase in resistance rates, government and hospital control policies are required to prevent the emergence of more resistant strains carrying new resistance factors.
Keywords: antimicrobials; CoNS; oxacillin; resistance; vancomycin